A high energy flux state attenuates the weight loss-induced energy gap by acutely decreasing hunger and increasing satiety and resting metabolic rate - Foright, Rebecca, author; Melby, Chris, advisor; Davalos, Deana, committee member; Wdowik, Melissa, committee member (Colorado State University. Libraries, 2014)
Introduction: Maintaining weight loss is one of the greatest challenges facing obese dieters. Weight loss-induced, compensatory, biological adjustments increase hunger and decrease resting metabolic rate (RMR), resulting in a disconnect between desired and required calories. This phenomenon, termed the energy gap, results in strong biological pressures that promote weight regain. Previous research in athletes has shown that high levels of physical activity coupled with high energy intake may increase RMR and reduce hunger. It is possible that this high energy flux state characterized by high daily energy expenditure (resulting from increased physical activity) with matching high energy intake (high calorie throughput) may attenuate the weight loss-induced energy gap by reducing hunger and increasing RMR. Methods: This proof-of-concept pilot study utilized a within-subjects cross-over experimental design. Six obese adults [age (x±SD: 42±12 y); BMI=35.7±3.7 kg/m2] underwent baseline measures of body weight, body composition, RMR via indirect calorimetry, fasting and post-prandial perceived hunger via visual analog scales, fasting and serial postprandial measures of glucose, insulin, and peptide YY (PYY, an anorexigenic hormone) and ad libitum energy intake from a mid-day food buffet. They then underwent weight loss (7% of initial body weight achieved over several months) and were stabilized at this reduced weight for three weeks. Subjects were then placed in two different 4-day experimental conditions of energy balance in random order--Low Flux (LF): sedentary with energy intake (EI)=RMR x1.35; and HF: daily exercise net energy cost of ~500 kcal/d and EI= RMR x1.7. On each morning of the 4 days of the HF and LF conditions, RMR was measured and hunger and satiety monitored. On the day following the HF and the LF conditions, respectively, participants again underwent measures of RMR, fasting and post-prandial hunger and satiety, fasting and serial postprandial measures of glucose, insulin, and PYY, and ad libitum energy intake from the food buffet. Results: Daily energy intake during HF (x±SD: 3,191±587 kcal/d) was significantly greater (p<0.001) than during LF (x±SD: 2,449±406 kcal/d), but in line with the experimental design, subjects were in energy balance and average weight did not differ between low flux (103±4.8 kg) and high flux (103.4±4.7 kg). Perceived hunger at the end of day was lower (p=0.020), fullness throughout the day was higher (p=0.015) and there was a trend for hunger throughout the day to be lower (p=0.091) in HF compared to LF conditions. Additionally, RMR was significantly higher in HF (1926±138 kcal/day) compared to LF (1847±126 kcal/day; P = 0.05). Fasting and post-prandial glucose concentrations did not significantly change with weight loss. Fasting and postprandial insulin concentrations were lower after weight loss the day following HF and LF compared to pre-weight loss baseline values, but did not differ by flux condition. Fasting PYY concentrations were not different among pre-weight loss, HF, and LF, but postprandial PYY was lower the day following HF compared to pre-weight loss baseline. Ad libitum food intake and subjective feelings of hunger and satiety on the day following HF and LF did not differ between flux conditions or from pre-weight loss baseline values. Conclusions: A 4-day high flux state resulted in decreased hunger, increased satiety and increased RMR in weight-reduced, weight-stable, obese individuals when compared to a low flux state. Our findings support the importance of a daily high energy flux state in attenuating the increase in hunger and the decrease in energy expenditure that accompany diet-induced weight loss. However, the greater satiety and lower hunger were not evident the day following the high flux state, suggesting that such benefits resulting from the acute state are not long-lasting.